1998
DOI: 10.1007/s001070050288
|View full text |Cite
|
Sign up to set email alerts
|

Particleboard I.B. forcast by TMA bending in UF adhesives curing

Abstract: Materials and methods Six urea-formaldehyde resins of molar ratios of U:F of respectively 1:1.1, 1:1.2, 1:1.3, 1:1.5, 1:1.8, and 1:2.0 were prepared as follows: To a urea/formaldehyde concentrate (formurea) containing 23% urea and 57% formaldehyde in water was added 22% NaOH to set the pH between 8.3-8.5. The temperature is raised in 50 minutes to 90 ~ maintaining the pH between 7.3-7.6 by small additions of 22% NaOH, and maintained at 90 ~ for approx 20 minutes. The pH decreases by itself and is maintained no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 3 publications
3
20
0
1
Order By: Relevance
“…Recent results have shown a clear correlation between the results of nonisothermal TMA curing in bending of aminoplastic and phenolic resinbonded wood joints and the IB strength of wood particleboard prepared using the same resin systems when the boards are prepared under welldefined and reproducible conditions. 30,31 The results shown in Table I for a series of low-condensation and low molecular mass PF resins confirm this finding. Thus, in Table I it is shown that the IB strength of wood particleboard bonded with low-condensation PF resins in which the initial 30,31 All these results confirm the well-known fact that an increase in molar ratio in a PF resin accelerates its curing, increases the IB strength of panels bonded with it, and decreases the TMA deflection (hence, increases the value of the bonded wood joint modulus) 1,30,31 (Fig.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Recent results have shown a clear correlation between the results of nonisothermal TMA curing in bending of aminoplastic and phenolic resinbonded wood joints and the IB strength of wood particleboard prepared using the same resin systems when the boards are prepared under welldefined and reproducible conditions. 30,31 The results shown in Table I for a series of low-condensation and low molecular mass PF resins confirm this finding. Thus, in Table I it is shown that the IB strength of wood particleboard bonded with low-condensation PF resins in which the initial 30,31 All these results confirm the well-known fact that an increase in molar ratio in a PF resin accelerates its curing, increases the IB strength of panels bonded with it, and decreases the TMA deflection (hence, increases the value of the bonded wood joint modulus) 1,30,31 (Fig.…”
Section: Resultssupporting
confidence: 64%
“…As the amount of urea addition moves to 30, 36, and 42%, the amount of unreacted urea increases; whereas it seems that for the substituted urea species, a stable maximum is attained, and the relative proportions of hydroxybenzyl urea becomes progressively higher than the proportion of bis(hydroxybenzyl) ureas. All this seems logical if we consider that, because in the resins tested the P : F molar ratio is 1 : 1.7, by increasing the percentage of urea added, the [P ϩ U] : F molar ratio decreases from 1 : 1.52 to, respectively, 1 : 1.44, 1 : 1.37, 1 : 1.1.31, 1 : 1.25, and 1 : 1.20 for the 12,18,24,30,36, and 42% level of urea substitution. Thus, it seems that the greater proportion of urea that coreacts usefully with the phenol in the PUF resin is attained at about 18% molar urea addition, although the proportion of copolymerized urea is still almost as high in the 12 and 24% urea addition resins.…”
Section: Resultsmentioning
confidence: 95%
“…A constant heating rate of 10°C/min was used. It must be remembered, however, that TMA tests used in this manner correlate mainly with the dry IB results of panels bonded with MUF resins and are no guarantee that correlation will exist with wet strength results in the case of new, experimental resin systems 5, 47–49. In this case, it is necessary to prepare wood particleboard to establish if such correlation exists 47–49.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that bond strength development goes through a first stage where mainly entanglement networks can develop , Laigle et al 1998, Zhao et al 1998). The network formed at this stage may be flexible enough to accompany elastic deformations and the duration of this stage may exceed the time taken to close the press.…”
Section: Discussionmentioning
confidence: 99%